Methodological bases of conceptology: features and structure of the linguo-cultural concept - Sakaeva, Liliya (2018)
In this article, two approaches to the studying the concept are investigated. The first approach defines concepts as complex, organized semantic forms. The second approach denotes that the concept and the term are used as synonyms and are interchangeable. As a result of the study of various interpretations of the term "concept", the following basic features of the concept are singled out:  the availability of the name; cognitive character (ability to process, store and transfer knowledge and experience); an open mental structure, capable to changes and transformations; verbalization through various linguistic units; cultural and historical reference; value character; presence of both verbal and non-verbal forms. The concept, being a unit of cognitive level, reflects a linguistic view of the world. It consists of perceptions and associations arising in the human mental process which are expressed by means of the verbal signs, concepts corresponding to them, the peculiar "labels" which have taken roots in our mind.